Rumus

cos(a+b)= cosa cosb- sina sinb
cos(a-b)= cosa cosb+ sina sinb
sin(a+b)= sina cosb+ cosa sinb
sin(a-b)= sina cosb+ cosa sinb

sin2a= 2 sina cosa

2 sina cosb= sin(a+b)+ sin(a-b)
2 cosa sinb= sin(a+b)- sin(a-b)
2 cosa cosb= cos(a+b)+ sin(a-b)
-2 sina sinb= cos(a+b)- cos(a-b)

Tinggalkan Balasan

Isikan data di bawah atau klik salah satu ikon untuk log in:

Logo WordPress.com

You are commenting using your WordPress.com account. Logout / Ubah )

Gambar Twitter

You are commenting using your Twitter account. Logout / Ubah )

Foto Facebook

You are commenting using your Facebook account. Logout / Ubah )

Foto Google+

You are commenting using your Google+ account. Logout / Ubah )

Connecting to %s

%d blogger menyukai ini: